Lateral and apical root resorption in teeth orthodontically moved into edentulous ridge areas - Adilson Luiz Ramos; Rodrigo Lorenzi Poluha; Pablo Guilherme; Gabriel Araújo Khoury; Joao Marcos Pedro Rosa Junior (Dental Press Editora, 2020)
ABSTRACT Objective: The present study aimed at comparing the external lateral root resorption (ELRR) and external apical root resorption (EARR) between teeth moved through the atrophic edentulous ridge and those undergoing the usual orthodontic movement. Methods: Fifty-four premolars were evaluated, where 27 of them had been moved toward the edentulous ridge (Group 1) and 27 from the same patient, had not been translated, which comprised the control group (Group 2). ELRR was evaluated by 0-3 scores and EARR was evaluated by 0-4 scores, before and after movement. Measurements were compared by Kruskal-Wallis and Student-Newman-Keuls tests. Results: ELRR increased statistically only in the Group 1 (p< 0.05). After orthodontic treatment, it was observed that almost 56% (n = 15) of teeth in Group 1 presented scores 2 and 3, while Group 2 presented scores 2 and 3 in about 11% (n= 3) of the teeth. EARR increased in both groups after orthodontic movement, however, statistically analyses showed no significant differences between groups (p> 0.05). Conclusions: Orthodontic movement into the atrophic edentulous ridge is subject to a greater lateral external root resorption.